THE PUBLIC ADMINISTRATION OF INVESTMENT ACTIVITY AT THE REGIONAL LEVEL IN UKRAINE: PROBLEMS AND DIRECTIONS OF IMPROVEMENT The - Fedorchak O.V. (Pressing Problems of Public Administration, 2017)
The article considers the essence of the system of public administration of investment activity at the regional level in Ukraine. It has been noted that separate functions of management of investment climate at the regional level are distributed between structural subdivisions of local state administrations and executive bodies of local self-government authorities. Part of the function of creating an investment climate is also carried out by regional development agencies. However, the cumulative powers of these institutions do not ensure the implementation of a fully- edged investment management process at the regional level.